1981
DOI: 10.1007/bf00426475
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of shuttle-box avoidance by combinations of orotic acid and central stimulants

Abstract: The effect of orotic acid and central stimulants on retention of shuttle-box avoidance was investigated in rats. Orotic acid (100 mg/kg) was injected 30 min before training; caffeine (20mg/kg), strychnine (1 mg/kg), or methylphenidate (10 mg/kg) were injected immediately after training. When given alone, these drugs improved avoidance retention when tested 24 h after training. However, improvement of retention was much more evident when orotic acid was given in combination with a stimulant. The data are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies reported that systemically-administered MPD enhances [5] , impairs [6−8] , or has no effect on learning and memory [9−12] . Systemically applied MPD could act throughout the central nervous system and would produce different or even divergent behavioral effects.…”
Section: The Psychostimulant Methylphenidate (Mpd; Also Called Ritalimentioning
confidence: 99%
“…Previous studies reported that systemically-administered MPD enhances [5] , impairs [6−8] , or has no effect on learning and memory [9−12] . Systemically applied MPD could act throughout the central nervous system and would produce different or even divergent behavioral effects.…”
Section: The Psychostimulant Methylphenidate (Mpd; Also Called Ritalimentioning
confidence: 99%